The Effect of Giving Effleurage Massage Techniques on Reduction of Labor Pain in Labor Pain in Women in Labor - Ani Retni; Harismayanti Harismayanti; Rianti P. Umani (PSPP JOURNALS, 2023)
Childbirth is the process of expelling the living products of conception from the uterus and then out through the birth canal, in the process of labor starting from the first stage with uterine contractions, dilatation and thinning of the cervix and descent of the fetus during labor accompanied by pain. Labor pain is characterized by uterine contractions, contractions starting at the 30th week of pregnancy which are called braxton hicks caused by irregular changes in the hormones estrogen and progesterone. Pain that accompanies uterine contractions affects the physiological mechanisms of a number of body systems which always cause a stress response so that Efforts are made to reduce labor pain, while one technique to relieve pain is massage effleurage technique. Effleurage massage is a massage technique using the palms of the hands in a circular motion pattern on several parts of the body. This technique can help distract and reduce anxiety. The role of Effleurage is to produce impulses that are sent through the cerebrum nerve fibers that are on the surface of the skin of these fibers, which can inhibit pain so that the brain cannot receive pain stimuli. The research method used is pre-experimental research with a pretest design post test one grub design is a measurement that is done before and after the study. In this study, it was shown that there was an effect of massage effleurage on reducing labor pain during the first stage of the latent phase in labor mothers.